B SERIES ENGINE PROPELLER MATCHING Studi Kasus Kapal Kontainer 100 TEUs - nurhadi nurhadi; Sumarsono Sumarsono (INFO-TEKNIK, 2017)
The alignment of the propulsion system on the vessel will greatly affect the magnitude of the resulting effectiveness to the speed of the vessel. To get a good system required a synchronization between the performance of propellers with the ship propulsion engine. Alignment that commonly known as engine propeller matching is done by finding the intersection between propeller characteristic graph with Thrust load coefficient at the operational point. The engine is adjusted as needed and can be optimally utilized based on the needs and characteristics of propeller.This paper will present propeller matching engines of propeller type B-Series 4-65 used on 100 TEUs Container Ships. Based on the load calculation results obtained propeller efficiency at 12 knots speed is only 0.43 far from the maximum efficiency that can be obtained. By using CAT 3516B engine type maximum speed 100% MCR that can be reached is 12 knots in rough hull condition.